Ang plano ni Elias - Naval, Blessy Joy Dagohoy; Dalena, Sari Raissa Ll. (2012)
"This thesis explores the phenomenon of diaspora and feminization of labor in the Philippines. Concepts from the New Economics of Migration Theory, Theory of Alienation and Feminist Film Criticism were employed in analyzing the study. The film recounts the story of a young Filipino family wherein the mother leaves for the first time as an Overseas Filipino Worker in Italy. Two days before she leaves, her six-year old son together with his playmate resort to various schemes to prevent her from leaving. From his young eyes he will learn that there is a greater world out there, more important than his toys and much, much bigger than him."
Vita.
Undergraduate thesis (A.B. Film and Audio Visual Communication)--University of the Philippines, Diliman.
Keywords: Ang Palno ni Elias (Short films).; Filipinos -- Employment -- Foreign countries